ChemInform Abstract: Anhydrides as α, β‐Unsaturated Acyl Ammonium Precursors: Isothiourea‐Promoted Catalytic Asymmetric Annulation Processes. Issue 40 (12th September 2013) - Robinson, Emily R. T.; Fallan, Charlene; Simal, Carmen; Slawin, Alexandra M. Z.; Smith, Andrew D.
Abstract Isothiourea HBTM 2.1 is utilized to generate functionalized chiral esters, dihydropyranones, or dihydropyridones in good yields and high enantioselectivities.